2017
DOI: 10.5194/bg-14-1383-2017
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of multi-century trends in the atmospheric CO<sub>2</sub> mean annual cycle in a prognostic ESM

Abstract: Abstract. The amplitude of the mean annual cycle of atmospheric CO 2 is a diagnostic of seasonal surface-atmosphere carbon exchange. Atmospheric observations show that this quantity has increased over most of the Northern Hemisphere (NH) extratropics during the last 3 decades, likely from a combination of enhanced atmospheric CO 2 , climate change, and anthropogenic land use change. Accurate climate prediction requires accounting for long-term interactions between the environment and carbon cycling; thus, anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Separate regional CO 2 tracers can be tracked independently and eventually summed to define a global response (e.g., refs. 1,16,22). In our simulation, each CO 2 tracer reflects surface fluxes from one tagged region.…”
Section: Methodsmentioning
confidence: 99%
“…Separate regional CO 2 tracers can be tracked independently and eventually summed to define a global response (e.g., refs. 1,16,22). In our simulation, each CO 2 tracer reflects surface fluxes from one tagged region.…”
Section: Methodsmentioning
confidence: 99%
“…For example, air and soil warming, in conjunction with a lengthening of the annual non-frozen period across the ABZ (Kim et al, 2012), stimulate plant productivity directly and indirectly through increased nutrient and water availability (Natali et al, 2014;Salmon et al, 2016). Warming and CO 2 fertilization have contributed to widespread "greening" across the ABZ, including shrubification (Myers- Smith et al, 2011Smith et al, , 2015 and northward treeline expansion (Lloyd and Fastie, 2003;Chapin et al, 2005), i.e., the encroachment of trees and shrubs into tundra regions. However, rapid warming across much of the ABZ is also accelerating decomposition, causing drought stress in warmer and drier landscapes (Carroll et al, 2011;Walker and Johnstone, 2014;Walker et al, 2015;Carroll and Loboda, 2017) and intensifying disturbance regimes such as wildfire and insect outbreaks (Turetsky et al, 2011;Kasischke et al, 2010;Rogers et al, 2018;Hanes et al, 2019), all of which contribute to the increasingly observed patterns of "browning" in the ABZ (Verbyla, 2011;Elmendorf et al, 2012;Phoenix and Bjerke, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in ASC in studies examining the multi-model TBM simulations combined with atmospheric transport modeling show that the simulated increase in seasonal amplitude of c a is generally underpredicted both at high altitude (Graven et al, 2013) and at remote surface stations (Thomas et al, 2016). It has been speculated that this is because TBMs underpredict CO 2 and/or warming effects on GPP (Forkel et al, 2016;Thomas et al, 2016), but changes in the seasonal cycle of ecosystem respiration (e.g., Liptak, Keppel-Aleks, & Lindsay, 2017), including winter respiration (Parazoo et al, 2016), must also be implicated.…”
mentioning
confidence: 99%